Proteome characterization of sugarcane primary cell wall - Rodrigues, Maria Juliana Calderan (2012)
This study provides information to support the use of plant cell wall, from sugarcane bagasse, to produce cellulosic ethanol. Therewith, cell wall proteins from sugarcane cells cultures, leaves and culms were identified. To do so, different protocols were used. Using two-month-old leaves and culms, the extractions were performed using a destructive method, based on griding the tissues, submitting them to a growing gradient of succrose and centrifugation, being the cell wall extract later isolated by washing on a nylon net. After that, the cell wall proteins were extracted using two salts, 0,2 M CaCl2 and 2 M LiCl. Using cultured cells, a similar protocol was used, but it had a previous step of separation of the cell wall through grinding and precipitation in glycerol 15%. Using culms of the same age, a nondestructive protocol was tested based on vacuum infiltration of the tissues in the same salts already described, 0,2 M CaCl2 and 2 M LiCl, and posterior centrifugation. Two replicates were used from two-month-old plants and three in the case of suspension cells. The complex samples were digested, fractionated and sequenced through mass spectrometry, using SYNAPT G2HDMS coupled to nanoACQUITY, both from Waters. Peptides were processed using ProteinLynx 2.5 Global Server against sugarcane translated-EST database. Using bioinformatic programs, such as Blast2GO, it was possible to find the annotation and classification of similar proteins. Only proteins equally found in all repetitions were considered in the main analysis. SignalP, WolfPSORT, TargetP, TMHMM and Predotar were used to predict the subcellular location, both from ESTs and blasted proteins, and only the proteins predicted to be secreted in two or more programs were considered as cell wall proteins. Altogether, 157 different SAS related to sugarcane cell wall were found. Among these, 101 different cell wall proteins were characterized from eight functional classes. The method based on vacuum infiltration seems to be the most efficient one, since it had almost half, 48,84% of the proteins predicted to be secreted, which is a good percentage when comparing to other studies. From secreted proteins most of them were related to lipid metabolism, as lipid-transfer proteins, oxido-reductases, such as peroxidases, cell wall modifying enzymes, like glycoside-hydrolases, proteases, proteins with interacting domains, signaling proteins and several others. Results are in agreement with the expected role of the extracellular matrix in polysaccharide metabolism and signaling phenomena. Therefore, this work provided valuable information about sugarcane cell wall that can lead to future studies to enhance cellulosic ethanol production.